A phase II trial of single oral FGF inhibitor, AZD4547, as second or third line therapy in malignant pleural mesothelioma. (February 2020) - Lam, Wei-Sen; Creaney, Jenette; Chen, Fred K.; Chin, Wee Loong; Muruganandan, Sanjeevan; Arunachalam, Sukanya; Attia, Mary S.; Read, Catherine; Murray, Kevin; Millward, Michael; Spiro, Jon; Chakera, Aron; et al.
Highlights: Patients with previously treated pleural mesothelioma were treated with AZD4547. 12 % of patients were progression free at 6 months. There were no confirmed objective responses to treatment. There was no association between tumour BAP1 protein expression and treatment outcome. This study did not meet its primary endpoint. Abstract: Objectives: Currently, there is no optimal salvage therapy for patients with malignant pleural mesothelioma (MPM) who relapse after treatment with first-line chemotherapy. In line with the strong preclinical rationale for targeting fibroblast growth factor receptor (FGFR) signalling in malignant mesothelioma, we conducted a phase II study assessing the efficacy of AZD4547, an oral tyrosine multi-kinase FGFR 1–3 inhibitor, as a second or third-line treatment. Materials and Methods: We conducted a single-center, open-label, single-arm phase II study of AZD4547 in eligible patients with confirmed, measurable MPM and radiological progression after first or second-line systemic chemotherapy. Patients received continuous, twice-daily oral AZD4547 on a 3-weekly cycle. The primary end point was 6-month progression free survival (PFS6). Response was assessed with CT scan every 6 weeks according to the modified RECIST criteria for mesothelioma (mRECIST) and toxicities were also assessed. The study used a Simon's two-stage design: 26 patients would be recruited to the first stage and more than 7 (27 %) of 26 patients were required to achieve PFS6 to continue to stage two, for a potential total cohort of 55 patients. Results: 3 of 24 patients (12 %) were progression-free at 6 months. Hence, the study fulfilled stopping criteria regardless of further recruitment and warranted discontinuation. The most common toxicities (across all grades) were hyperphosphatemia, xerostomia, mucositis, retinopathy, dysgeusia, and fatigue. Maximum toxicities were grade 2 or below for all patients across all cycles. There was no association between tumour BAP1 protein loss and clinical outcomes. Conclusions: The FGFR 1–3 inhibitor AZD4547 did not demonstrate efficacy in patients with MPM who had progressed after first line treatment with platinum-based chemotherapy.